IMMIGRATION OF DAGESTANIS TO THE OTTOMAN EMPIRE DURING THE CAUCASIAN WAR (1820S–1850S) - Cociev, Georgij Vital'evic (History, Archeology and Ethnography of the Caucasus, 2023)
The purpose of this study is to identify the facts of immigration of Dagestanis to the Ottoman Empire during the Caucasian War, the main areas of their settlement and the features of their socio-economic and political adaptation there. At a fairly early stage of the Russian military-political expansion in the North-Eastern Caucasus the Ottoman state became attractive as a place of emigration for some members of the Dagestan elite involved in the confrontation with the Russian forces, due not only to the current international-political situation but also to the long-standing ties of many khanates and jamaats with Istanbul and the corresponding expectations for a favorable reception. A noticeable category of migrants was made up of persons of clergy, who enjoyed the special care of the Porte and included both purely religious immigrants who aspired to settle in the Hijaz and other Muslim centers of the empire, and Sufi communities presumably involved in the resistance movement in the Caucasus with certain revanchist aspirations in relation to their abandoned homeland. From the beginning of the 1850s, agrarian (peasant) groups came to the fore among the muhajirs, usually led by the ulemas, but often settled by the authorities separately from them in rural areas with limited material assistance. Despite the trend towards a gradual increase during the period under review of the influx of Dagestanis to the Sultan’s dominions, the total number of immigrants hardly exceeded 1–2 thousand people settled in the cities and villages of Anatolia, the Arab provinces and the Balkans. The paper is based on an analysis of mainly Turkish archival sources, a significant part of which is being introduced into scientific circulation for the first time.
Keywords: Dagestan; Caucasian War; Ottoman Empire; immigration; colonization; adaptation